Identification and validation of an immune-related gene prognostic signature for clear cell renal carcinoma - Hua, Shan; Xie, Zhiwen; Zhang, Yongqing; Wu, Lei; Shi, Fei; Wang, Xingjie; Xia, Shujie; Dong, Shengli; Jiang, Juntao (Frontiers in Immunology, 2022)
Clear Cell Renal Carcinoma (ccRCC) accounts for nearly 80% of renal carcinoma cases, and immunotherapy plays an important role in ccRCC therapy. However, the responses to immunotherapy and overall survival for ccRCC patients are still hard to predict. Here, we constructed an immune-related predictive signature using 19 genes based on TCGA datasets. We also analyzed its relationships between disease prognosis, infiltrating immune cells, immune subtypes, mutation load, immune dysfunction, immune escape, etc. We found that our signature can distinguish immune characteristics and predict immunotherapeutic response for ccRCC patients with better prognostic prediction value than other immune scores. The expression levels of prognostic genes were determined by RT-qPCR assay. This signature may help to predict overall survival and guide the treatment for patients with ccRCC.